Potential probiotic Lactiplantibacillus plantarum DS1800 extends lifespan and enhances stress resistance in Caenorhabditis elegans model - Kim, Seunghyun; Lee, Yu-Ri; Yang, Haneol; Park, Chan-Hyeok; Yun, Chan-Seok; Jang, Byung-Chun; Hong, Yeongjin; Park, Doo-Sang (Frontiers in Physiology, 2024)
Probiotics are live microorganisms that provide health benefits when administered in appropriate amounts by improving or restoring the balance of intestinal microbiota. Various functional probiotic products have been developed due to the growing interest in the health-promoting and anti-aging effects of enhancing the gut microbiome. Lactiplantibacillus plantarum species are known for their potential to extend lifespan. However, this activity is strain or isolation source specific, necessitating the identification of individual strain functionalities. This study used the C. elegans model to screen probiotics for life-extension effects and analyze their functions. The 43 lactic-acid bacteria strains isolated from fermented foods, breast milk, and human feces were subjected to longevity assays, and L. plantarum DS1800 was selected to demonstrate the most effective lifespan extension. The average lifespan of Caenorhabditis elegans fed DS1800 increased by 17.36% compared with those fed Escherichia coli OP50. Further analysis of the expression of key genes related to longevity revealed the high expression of the skinhead-1 (skn-1), antibacterial, and heat stress resistance genes via the p38 MAPK pathway. These expression patterns suggest that DS1800 extends the lifespan of C. elegans by enhancing its stress resistance and protecting it against pathogens. Additionally, DS1800 exhibited excellent intestinal adhesion, with 7.56% adhesion to HT-29 cells. Therefore, L. plantarum DS1800 is effective in extending the lifespan of C. elegans and can be used as a functional probiotic.